2020
DOI: 10.1097/md.0000000000022953
|View full text |Cite
|
Sign up to set email alerts
|

Influence of parental education levels on eating habits of pupils in Nigerian primary schools

Abstract: This study investigated the eating habits of pupils in Nigerian primary schools based on the respective education levels of their parents. Data were obtained using the Child Eating Behavior Questionnaire (CEBQ). Participants included a total of 144 pupils who were purposively selected from 6 primary schools. Based on responses, a cross-sectional analytic study design was implemented to investigate how parental education levels (PELs) influenced the eating habits of their children. Data assessment wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…They play a crucial role in imparting their knowledge to their adolescent children through conversations, acting as role models, and creating an environment that supports healthy eating habits [ 54 ]. Parental education is frequently associated with higher socioeconomic status, which can further influence adolescents’ access to resources and opportunities for healthy eating [ 55 , 56 ]. The advantages of the educational environment in urban areas, as mentioned above, contribute to improved knowledge and positive attitudes toward healthy eating among adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…They play a crucial role in imparting their knowledge to their adolescent children through conversations, acting as role models, and creating an environment that supports healthy eating habits [ 54 ]. Parental education is frequently associated with higher socioeconomic status, which can further influence adolescents’ access to resources and opportunities for healthy eating [ 55 , 56 ]. The advantages of the educational environment in urban areas, as mentioned above, contribute to improved knowledge and positive attitudes toward healthy eating among adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Parental-related factors, including the education level and the primary caregiver, were also shown to contribute to determining adolescents' nutrition literacy level in the present study. In this regard, one study showed that low-educated parents typically have children with unhealthy eating habits ( 53 ). The family structure that a child grows up in will actively participate in developing and supporting behaviors that will stick with him or her throughout their life.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing number of current studies which suggest that nutrition education and nutritional counselling are very much required to improve the eating behaviours of students at the Nigerian basic education level [18][19] [20]. Hegazy et al [21] stated that the provision of nutritional counselling might be related to substantial improvement in individual's dietary outcomes, nutritional knowledge, nutritional practices, health status and their feat in daily life activities.…”
Section: Introductionmentioning
confidence: 99%